The Magneticreactive Effect in Transistors for Construction Transducers of Magnetic Field - Osadchuk, V. S.; Osadchuk, A. V. (Elektronika ir Elektrotechnika, 2011)
In the given article the method of build-up of radiomeasuring transducers of a magnetic field on a basis magneticreactive effect in bipolar and field-effect transistors is offered. It is shown, that change of a reactive component of a complete resistance from induction density on electrodes a source - drain of a field-effect transistor makes 0,6 Ohm/mT, and for the bipolar transistor on electrodes the emitter-collector - 12,5 Ohm/mT. Such changes of reactive components of a complete resistance are essential, that confirms an opportu-nity of practical application of these effects for making microelectronic radiomeasuring transducers. The circuit of the transducer of a magnetic field on field-effect transistors which sensitivity makes from 510 up to 3500 Hz/mT is offered. Ill. 3, bibl. 8 (in English; ab-stracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.109.3.185